High-Time-Resolution Astrophysics using the Thai 2.4-m Telescope with Ultraspec. Issue Volume 14:Issue S339(2018) (November 2017) - Irawati, P.
Abstract: The Thai National Observatory (TNO) is equipped with a 2.4-m Ritchey-Chretien telescope and the high-speed versatile Ultraspec camera. The instrument employs a low-noise frame-transfer EMCCD, suitable for the observation of faint objects and for high-time-resolution astrophysics. We present some of the results obtained in the first four years of operation, focusing particularly on fast photometry of lunar and stellar occultations, and follow-up efforts on a few white-dwarf binaries. Among the latter is the polar cataclysmic variable UZ For. This system displays period changes and is suspected of hosting circumbinary planets. Our high-speed photometry data show a decreasing trend in the O–C diagram of UZ For. Using our new data set, we will investigate whether the period change in this binary is due to a possible third body, or to other mechanism(s).